If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 91 + -1(5x + 16) = 5(x + 4) + x Reorder the terms: 91 + -1(16 + 5x) = 5(x + 4) + x 91 + (16 * -1 + 5x * -1) = 5(x + 4) + x 91 + (-16 + -5x) = 5(x + 4) + x Combine like terms: 91 + -16 = 75 75 + -5x = 5(x + 4) + x Reorder the terms: 75 + -5x = 5(4 + x) + x 75 + -5x = (4 * 5 + x * 5) + x 75 + -5x = (20 + 5x) + x Combine like terms: 5x + x = 6x 75 + -5x = 20 + 6x Solving 75 + -5x = 20 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 75 + -5x + -6x = 20 + 6x + -6x Combine like terms: -5x + -6x = -11x 75 + -11x = 20 + 6x + -6x Combine like terms: 6x + -6x = 0 75 + -11x = 20 + 0 75 + -11x = 20 Add '-75' to each side of the equation. 75 + -75 + -11x = 20 + -75 Combine like terms: 75 + -75 = 0 0 + -11x = 20 + -75 -11x = 20 + -75 Combine like terms: 20 + -75 = -55 -11x = -55 Divide each side by '-11'. x = 5 Simplifying x = 5
| 36-(2x+5)=2(x+8)+x | | 4x-10-1x+3=14 | | 12.5/x=75/600 | | -1/4y-1=14.5 | | a^4b^-3/(a^2b^-3)^-2 | | -1/4y-1=14 | | 3n-10=6n-20 | | 5(b-x)=a(x-2) | | -2*2n+3=8 | | 4*x-2-12=0 | | 7y-2y-84=2y-2y+61 | | (3a+b)-bx=a(x-2) | | N^3-6n^2-4n+24=0 | | 9x-(4x-10)=50 | | 27r^3+125=0 | | 16z^2-40z+25=0 | | ((100x^2)/16)-(4y/49) | | 156.25+5.75x=7x | | 32-12y+y^2=0 | | -64b^2+0z+25=0 | | 25-64b^2=0 | | 13/7(1/2) | | 13/1 | | 8z^2-88z+240=0 | | 7+8v=6+8v | | 3in+X=11in | | X+3in=11in | | 2(x+1)-3(x-1)=5-x | | 2(x+1)-3(x-1)=5-1 | | 3*ln(e)= | | 9(x-10)=-27 | | .20=x^2/85-x |